2014
DOI: 10.1017/s1368980013003431
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a self-administered FFQ in adults in Argentina, Chile and Uruguay

Abstract: Objective: To assess the reproducibility and validity among adults in the Southern Cone of Latin America (Argentina, Chile and Uruguay) of a self-administered FFQ to be used in the CESCAS I Study, an ongoing observational prospective cohort study to detect and follow up CVD and their risk factors, as well as in other epidemiological studies. Design: Relative validity of the FFQ was evaluated by comparing nutrient and selected food group intakes with those from three 24 h recalls (24HR) administered over 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 30 publications
5
32
2
4
Order By: Relevance
“…This could have happened because in the second administration of the FFQ the participants could quantify their food intake more precisely due to the familiarity with the FFQ methodology. These findings are consistent with results of other studies in similar 10,11 and different populations [12][13][14][15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could have happened because in the second administration of the FFQ the participants could quantify their food intake more precisely due to the familiarity with the FFQ methodology. These findings are consistent with results of other studies in similar 10,11 and different populations [12][13][14][15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
“…The energy and macronutrient intakes observed in this study were similar to that obtained by Dehghan et al through 24-hour recall 10 . On the other hand, Elorriaga et al 11 obtained lower values of energy and nutrients intakes, possibly because of the sampling selection of the study, which was done in primary-care clinics. In their study, the mean age of the sample was higher, which could have resulted in a lower mean intake compared with our results 11 .…”
Section: Discussionmentioning
confidence: 94%
“…Among micronutrients, highest correlation coefficients were seen for vitamin D, Mg and Se. High correlation coefficients between FFQ and 24 h recall have been reported for vitamin D by Elorriaga et al (33) and Streppel et al (34) . Toft et al (32) and Johansson et al (35) found correlations for saturated fat of the same magnitude as in the present study when comparing FFQ and 24 h recalls.…”
Section: Discussionmentioning
confidence: 81%
“…Our NQ validity indicators are comparable to those reported by other local authors using different methodology. 13,15 In fact, a validation study of FFQ vs. 24 h-DR conducted in urban Rosario, Argentina, in a comparable age-group, reported similar r-values for energy and fat intake and lower levels for protein and carbohydrate intake. 13 A survey in southern Latin America (Argentina, Chile, and Uruguay) using a FFQ in a 21---74-year age-group found comparable results.…”
Section: Second Phasementioning
confidence: 95%
“…Therefore, these prerequisites permit only self-administered tools. Of the existing, validated tools for assessing food intake in Argentina 12,13 and the Southern Cone of Latin America, 14,15 only one is self-administered 16 ; however, all these measures are FFQs or 24 h-DR.…”
Section: Q1mentioning
confidence: 99%